Predictive study of academic stress with the irritable bowel syndrome in medicine students at a public university in Mexico. Issue 1 (1st January 2018) - Pozos-Radillo, Elizabeth; Preciado-Serrano, Lourdes; Plascencia-Campos, Ana; Morales-Fernández, Armando; Valdez-López, Rosa
ABSTRACT: Background : Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder associated with stress, which may appear by an educational context, given that students are exposed to demands in the academic environment during their education process that may lead to developing diseases. This study reports on the relationship between the IBS and academic stress and compares results of men and women. Methods : A random survey was made of 561 medicine students at a public university in Mexico. The ROMA III criteria were used for the IBS and the Academic Stress Inventory for academic stress. A multiple regression analysis was made. Results : The results showed that students with academic overload and lack of time are at risk for developing the IBS. Conclusions : Therefore, the recommendation is to implement educational programs aiming at self-care as well as gaining knowledge about academic stress-related factors and the physical responses that may result in repercussions with serious consequences for student life such as pain, disease and dropping out of school.